IMPROVING THE TENTH GRADE STUDENTS’ ENGLISH SPEAKING ABILITY THROUGH STORYTELLING - Firdayanti Firdaus; Dwi Suci Amaniarsih (English Review: Journal of English Education, 2018)
The purposes of this research are to find out; 1) how to improve English speaking ability of the tenth grade students at Harapan-I Medan through the application of storytelling method, and 2) how the students’ responses to storytelling as a learning method. This research was a Classroom Action Research applying Kemmis McTaggart Model.  The research was done in two cycles in which each cycle consists of four stages: plans, actions, observations, and reflections. The subjects in this research were students of Grade X-6 of Senior High School Harapan-I Medan. The object of this study was the application of the Storytelling method to improve the students’ English speaking ability. Based on the results of the research, it was found that the percentage of completeness from pre-action, Cycle-I, and Cycle-II increased at Senior High School Harapan-I Medan. The percentage of student’s completeness in pre-action was 27%, in the Cycle-I was 47%, and in the Cycle-II was 70%. There was a significant increase (43%) from pre-action, cycle-I, and cycle-II. In addition, students’ enthusiasm, courage, and activity have also increased. Thus, it can be concluded that storytelling method has improved the speaking ability of the tenth grade students of Senior High School Harapan-I Medan and increased their response, enthusiasm, courage, and activity to speak English.Keywords: speaking ability; English; storytelling; folklore; classroom action research.